THE IMPACT OF IMPLEMENTING CLOUD COMPUTING-BASED ACCOUNTING INFORMATION SYSTEM ON BUSINESS PERFORMANCE - Muhammad Saddam Ramadhan; Dian Indri Purnamasari (Akmenika: Jurnal Akuntansi dan Manajemen, 2026)
This research aims to analyze the influence of cloud computing-based accounting information systems on the business performance of MSMEs in Sleman Regency. Using the Technology Acceptance Model (TAM) and the Diffusion of Innovation Theory, this research examines five variables: relative advantage, perceived ease of use, perceived usefulness, complexity, and software. The population in this study is the MSMEs in Sleman Regency. The data used in this study are primary data from 100 respondents using purposive sampling. The results of this study indicate that certain variables, such as relative advantage, perceived usefulness, perceived ease of use, and software, have a positive effect on business performance. Furthermore, the complexity variable does not influence business performance. Cloud computing enables MSMEs to enhance efficiency, security, and data accessibility at a lower cost, thereby improving productivity. Despite the advantages, challenges such as technology complexity and data security persist, requiring careful implementation and training of human resources. This study contributes to the understanding of digital technology adoption among MSMEs and offers insights for policymakers and business practitioners aiming to improve MSME performance through technological integration